Of spies and spokesmen my life as a Cold War correspondent - Daniloff, Nicholas, 1934- (University of Missouri Press, 2008)
"A riveting look at Cold War journalism behind the Iron Curtain by a Russian-American reporter who was later falsely accused of spying and thrown into a Russian prison. Daniloff sheds light on such prominent figures as Nikita Khrushchev, Henry Kissinger, and suspected spies Frederick Barghoorn, John Downey, and Sam Jaffe"--Provided by publisher.